Emotional intelligence as an indicator of coping Skills among undergraduate dental students at Peshawar: a correlational study - Basheer Rehman; Brekhna Jamil; Admin (Journal of the Pakistan Medical Association, 2020)
Objective: The objective of this study is to determine correlation between emotional intelligence and academic stress. Methodology: This quantitative correlational study was conducted in Khyber College of Dentistry Peshawar. A total of 298 undergraduate dental students from first year to final year session 2015-16 of all ages and genders were included in this study. Emotional intelligence score Dental Environmental Stress were calculated using Mean and SD. A one way ANOVA & Tukey Post hoc tests were performed for Emotional Intelligence and academic stress separately to compare the mean difference between academic groups. A spearman correlation coefficient was used to check relationship between Emotional Intelligence and academic stress with different academic levels. EI and academic stress were correlated using Pearson Correlation. Results: Out of 298 students, 98 (32.89%) were males and 200 (67.11%) were females with a male to female ratio of 2.04:1. The mean EI score of all the BDS students from first year to final year was 81.23 ± 22.8. The total mean DES score of all classes was 109.54 ± 19.5 with a trend of decreasing stress levels from first year to final year. A Pearson correlation test was run. Statistically significant (r:-.766: P Value: .001, N: 298) negative strong relationship between EI and academic stress exists. Conclusion: The gradual increase of EI from first year to final year showing the importance of teaching and learning methods which incorporate certain trends of EI in the students overall training. Key words: Emotional Intelligence, Coping skills, Undergraduate dental students